Venous surgery for the treatment of chronic venous insufficiency with respect to global venous haemodynamics and clinical symptoms - Strölin, A.; Häfner, H.-M.; Rühle, M.; Breuninger, H.; Schippert, W.; Möhrle, M.; Jünger, M. (Phlebologie, 2009)
Our goal was to document changes in venous drainage function ΔV and venous refill times to and th achieved with venous surgery and compare them with preoperative measurements acquired using a variety of venous function tests. Preoperative measurements were performed with two pressure cuffs to predict postoperative outcome; they were compared with actual postoperative measurements made without a pressure cuff. In addition we also analyzed whether the postoperative improvement in venous haemodynamics was correlated with an improvement in clinical findings and symptoms. Patients, methods: 64 patients (14 men and 50 women) were enrolled into the study. Inclusion criteria were Doppler sonographic evidence of insufficiency of the saphenous veins and impaired venous haemodynamics, which form the medical indication for venous surgery. Before and after surgery a variety of diagnostic tests of venous function were carried out simultaneously with the patient in a seated position and performing dorsal extensions: mercury strain gauge plethysmography (MSGP) at the forefoot and calf, phlebodynamometry (PDM), light reflection rheography (LRR), digital photoplethysmography (DPPG) with Elcat measuring head and with Laumann Elcat measuring head, universal light reflection plethysmography (ULP). Results: All the examined methods are suitable for monitoring progress and evaluating therapeutic success after the selective surgical removal of insufficient vein segments. All examination methods showed that refill times t0 and th were significantly improved 6 weeks after venous surgery. The postoperative results of ΔV, t0 and th were most reliably predicted by MSGP (forefoot). ΔV, to and th values determined with MSGP at the calf differed significantly from those acquired with PDM, so MSGP (calf) should not be used for preoperative screening. Conclusions: A close correlation between improvement of clinical symptoms and improvement in venous haemodynamics was found. Selection of the suitable preoperative measurement method makes it possible to accurately predict postoperative outcome.
Keywords: Dynamic venous function tests; CVI; surgical treatment; clinical outcome